A comparative study of early and late extubation following transoral odontoidectomy and posterior fixation - Manish Marda; Mihir Prakash Pandia; Girija Prasad Rath; Shashank Sharad Kale; Harihara Dash (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Elective ventilation is the usual practice after transoral odontoidectomy (TOO) and posterior fixation. This practice of elective ventilation is not based on any evidence. The primary objective of our study was to find out the difference in oxygenation and ventilation in patients extubated early compared to those extubated late after TOO and posterior fixation. The secondary objectives were to compare the length of Intensive Care Unit (ICU)/hospital stay and pulmonary complications between the two groups. Material and Methods: After TOO and posterior fixation, patients were either extubated in the operating room (Group E) or extubated next day (Group D). The oxygenation (PaO 2 :FiO 2 ratio) and ventilation (PaCO 2 ) of the two groups before surgery, at 30 min and at 6/12/24 and 48 h after extubation were compared. Complications, durations of ICU and hospital stay were noted. Results: The base-line PaO 2 :FiO 2 and PaCO 2 was comparable between the groups. No significant change in the PaO 2 : FiO 2 was noted in the postoperative period in either group as compared to the preoperative values. Except for at 12 h after surgery, there was no significant difference between the two groups at various time intervals. No significant change in the PaCO 2 level was seen during the study period in either group. PaCO 2 measured at 30 min after surgery was more in Group E (37.5 ± 3.2 mmHg in Group E vs. 34.6 ± 2.9 mmHg in Group D), otherwise there was no significant difference between the two groups at various time intervals. One patient in Group E (7.1%) and two patients in Group D (13%) developed postoperative respiratory complication, but the difference was not statistically significant. The mean ICU stay (Group D = 42 ± 25 h vs. Group E = 25.1 ± 16.9 h) and mean hospital stay (Group D = 9.9 ± 4 days vs. Group E = 7.6 ± 2.2 days) were longer in Group D patients. Conclusion: Ventilation and oxygenation in the postoperative period in patients undergoing TOO and posterior fixation are not different between the two groups. However, the duration of ICU and hospital stay was prolonged in group D.